THE EFFECT OF ERGONOMIC GYMNASTICS ON DECLINE CHOLESTEROL IN PERIMENOPAUSAL PKK MOTHERS LALANG VILLAGE, MEDAN SUNGGAL DISTRICT IN 2021 - Charin Charin; Irwansyah Siregar (Indonesia Sport Journal, 2021)
This study aims to determine the effect of ergonomic exercise on reducing cholesterol in perimenopausal PKK mothers in 2021 in the sub-district of Medan Sunggal, and this study will be conducted by means of pre-test and post-test. This research method is an experimental method (treatment) with data collection techniques involving two variables, one independent variable, namely ergonomic exercise and one variable, namely cholesterol levels. The data analysis technique used t-test with the help of the SPSS program. Based on the research, it turns out that from the calculation results obtained > where 5,10 > 2,26, so Ho is rejected and Ha is accepted.So it can be said that there is a significant effect of ergonomic exercise on reducing cholesterol levels in PKK mothers. The results of this study involved 23 populations, and according to the category there were 10 samples of PKK mothers. Keywords: Ergonomic exercise, Cholesterol